Sensitive Logic Nanodevices with Strong Response for Weak Inputs. Issue 11 (24th January 2022) - Lv, Wen Yi; Li, Chun Hong; Yang, Fei Fan; Li, Yuan Fang; Zhen, Shu Jun; Huang, Cheng Zhi
Abstract: Sensitive sensing is critical when developing new calculation systems with weak input signals (ISs). In this work, a "weak‐inputs‐strong‐outputs" strategy was proposed to guide the construction of sensitive logic nanodevices by coupling an input‐induced reversible DNA computing platform with a hybridization chain reaction‐based signal amplifier. By rational design of the sequence of computing elements (CEs) so as to avoid cross‐talking between ISs and signal amplifier, the newly formed logic nanodevices have good sensitivity to the weak ISs even at low concentrations of CEs, and are able to perform YES, OR, NAND, NOR, INHIBIT, INHIBIT‐OR and number classifier operation, showing that the DNA calculation proceeds in dilute solution medium that greatly improves the calculation proficiency of logic nanodevices without the confinement of the lithography process in nanotechnology. Abstract : In this work, a "weak‐inputs‐strong‐outputs" strategy was proposed to guide the construction of different sensitive logic nanodevices that have a strong response for weak input signals by coupling an input‐induced reversible DNA computing platform with a hybridization chain reaction‐based signal amplifier.